Hatching Characteristics of Japanese Quail Eggs in a Tropical Environment - Daikwo, S.I.; Dim, N.I.; Momoh, M.O. (International Journal of Poultry Science, 2011)
A study to evaluate hatching characteristics of incubated Japanese quail eggs in Nigeria was conducted. A total of 1,116 eggs were incubated in 3 batches in a still-air kerosene incubator. The results showed that mean early and late embryonic mortality on the basis of fertile eggs were 18.59±1.85 and 9.89±1.31%, respectively. Mean fertility, hatchability of fertile eggs, hatchability of total eggs set and weight of newly hatched chicks were 85.41±1.25%, 71.52±1.94%, 61.31±1.93% and 6.47±0.10 g, respectively. Hatching chick weight was found positively and significantly (p